Mayors in the middle : politics, race, and mayoral control of urban schools - Henig, Jeffrey R., 1951-; Rich, Wilbur C. (Princeton paperbacks., 2004)
Desperate to jump-start the reform process in America's urban schools, politicians, scholars, and school advocates increasingly are looking to mayors for leadership. But does a stronger mayoral role represent bold institutional change with real potential to improve big city schools, or just the latest in the copycat world of school reform du jour? Is it democratic? Why have efforts to put mayors in charge so often generated resistance along racial dividing lines? Public debate and scholarly analysis have shied away from confronting such issues head on. Mayors in the Middle brings together, for students of education policy and urban politics as well as scholars and school advocates, the most thoughtful and original analyses of the promise and limitations of mayoral takeovers of schools.